KEPATUHAN DIET DAN LAMANYA HEMODIALISA BERPENGARUH TERHADAP KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK - Kamaruddin Tone; Badar Badar; Lukman Nulhakim (Bajang Institute, 2023)
The process of hemodialysis therapy, which tooks 5 hours, will generally cause physical stress to patients after hemodialysis. Patients will feel fatigue, headaches and cold sweats due to decreased blood pressure, in connection with the effects of hemodialysis (Black & Hawks, 2014; Said & Mohammed, 2013; Sudoyo, Aru W, 2007; Suhardjono, 2014).The purpose of this study was to determine the correlation between dietary adherence and duration of hemodialysis with the quality of life of chronic kidney failure patients at Taman Husada Bontang Hospital. The research design used is correlation with the approach method carried out using cross sectional. Sampling in this study is total sampling by taking the same number of samples as the population. So the sample size used in this study was 35 respondents. Data analysis using Chi-quare test with a value of 0.05 (p-value <0.05). The results of the pearson chi square test obtained a sig value (2-sided) with a result of 0.000 p value <0.05 to 0.000<0.05 showed a relationship between dietary compliance with quality of life while the relationship between hemodialysis duration and quality of life the results of the pearson chi square test signification value were 0.000 <0.05 so that the hypothesis could be accepted. From the analysis data above, it can be concluded that the more obedient a patient is to maintain his diet and the duration of hemodialysis greatly affects his quality of life. Therefore, researchers hope that kidney failure patients undergoing hemodialysis therapy continue to maintain their diet strictly as recommended to stay a quality life.